Altruism As a Motive For Implementing Community Welfare Programs Through Islamic Philanthropic Funds: Case Study of Baitul Maal Hidayatullah Empowerment Actors - Annisa Qurrota A'yun; Haryani Saptaningtyas; Widiyanto Widiyanto (Ijtimā iyya Journal of Muslim Society Research, 2022)
This paper will discuss the altruistic motives of actors implementing social welfare programs originating from the utilization of Islamic philanthropic funds during the issue of identity politics in Indonesia. This study is based on the motives that actors should have in implementing social welfare programs that utilize Islamic religious, philanthropic funds that uphold fair welfare. Altruism motives reflect the goals of Islamic philanthropy. The research was conducted using a qualitative approach with motive analysis using discourse texts because of interviews with informants from Hidayatullah and Baitul Maal Hidayatullah, which were connected to the theory to produce conclusions. The objects in this study are empowerment actors from religious-based social organizations, Hidayatullah. The research results explain that aspects of altruism, starting from the encouragement, actions, and goals of the actors in Baitul Maal Hidayatullah, have similarities that lead to community welfare so that altruism motives reflect what they do as implementing welfare programs based on the Islamic religion. Hidayatullah's foundation regarding practical politics that is not implemented is the basis for actors in carrying out the empowerment process for the community’s welfare.